miRNA-Mediated Mechanisms in the Generation of Effective and Safe Oncolytic Viruses - Mariia Toropko; Sergey Chuvpilo; Alexander Karabelsky (MDPI AG, 2024)
MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression by inhibiting the translation of target transcripts. The expression profiles of miRNAs vary in different tissues and change with the development of diseases, including cancer. This feature has begun to be used for the modification of oncolytic viruses (OVs) in order to increase their selectivity and efficacy. OVs represent a relatively new class of anticancer drugs; they are designed to replicate in cancer tumors and destroy them. These can be natural viruses that can replicate within cancer tumor cells, or recombinant viruses created in laboratories. There are some concerns regarding OVs' toxicity, due to their ability to partially replicate in healthy tissues. In addition, lytic and immunological responses upon OV therapy are not always sufficient, so various OV editing methods are used. This review discusses the latest results of preclinical and clinical studies of OVs, modifications of which are associated with the miRNA-mediated mechanism of gene silencing.